Singing - Irons, J. Yoon; Hancox, Grenville (Arts for health, 2021)
We are 'hard-wired' to sing - singing has defined our evolution. Through singing we express our feelings, communicate and connect with others. We are all singers: singing is part of us and defines cultures worldwide. Singing also, importantly, makes us feel better: it is, undoubtedly, good for us. This book provides an important overview of current research showing the benefits of singing on our health and wellbeing. Case studies illustrate its power - for example, how singing helps hospitalised children and a man living with Parkinson's. The book also discusses potential barriers for singing and useful strategies needed to overcome them. An example of a community singing group is also demonstrated, alongside practical advice on facilitating community singing groups for health and wellbeing. The book will be valuable to professionals working in health and social care settings, to practitioners and educators interested in engaging in singing for health promotion, and individuals looking to find out more about the benefits and practicalities of singing.